Nystagmus in Childhood - Eleni Papageorgiou; Rebecca J. McLean; Irene Gottlob (Pediatrics and Neonatology)
Nystagmus is an involuntary rhythmic oscillation of the eyes, which leads to reduced visual acuity due to the excessive motion of images on the retina. Nystagmus can be grouped into infantile nystagmus (IN), which usually appears in the first 3–6 months of life, and acquired nystagmus (AN), which appears later. IN can be idiopathic or associated to albinism, retinal disease, low vision, or visual deprivation in early life, for example due to congenital cataracts, optic nerve hypoplasia, and retinal dystrophies, or it can be part of neurological syndromes and neurologic diseases. It is important to differentiate between infantile and acquired nystagmus. This can be achieved by considering not only the time of onset of the nystagmus, but also the waveform characteristics of the nystagmus. Neurological disease should be suspected when the nystagmus is asymmetrical or unilateral. Electrophysiology, laboratory tests, neurological, and imaging work-up may be necessary, in order to exclude any underlying ocular or systemic pathology in a child with nystagmus. Furthermore, the recent introduction of hand-held spectral domain optical coherence tomography (HH SD-OCT) provides detailed assessment of foveal structure in several pediatric eye conditions associated with nystagmus and it can been used to determine the underlying cause of infantile nystagmus. Additionally, the development of novel methods to record eye movements can help to obtain more detailed information and assist the diagnosis. Recent advances in the field of genetics have identified the FRMD7 gene as the major cause of hereditary X-linked nystagmus, which will possibly guide research towards gene therapy in the future. Treatment options for nystagmus involve pharmacological and surgical interventions. Clinically proven pharmacological treatments for nystagmus, such as gabapentin and memantine, are now beginning to emerge. In cases of obvious head posture, eye muscle surgery can be performed to shift the null zone of the nystagmus into the primary position, and also to alleviate neck problems that can arise due to an abnormal head posture.